KONSEP PENDIDIKAN SEUMUR HIDUP: TINJAUAN TEORITIS, IMPLEMENTASI KEBIJAKAN, DAN TANTANGAN DI ERA DIGITAL INDONESIA - Fahriana; Habib Anwar Al-Anshari (STKIP Subang, 2026)
Lifelong education is a strategic instrument for maintaining individual relevance amidst the rapid dynamics of technology, economics, and social shifts. However, in Indonesia, the implementation of this concept remains fragmented between lagging conventional non-formal pathways and digital skills enhancement programs that tend to be exclusionary. This study is crucial for identifying systemic barriers to lifelong education policy and formulating a more inclusive direction for integration. This research employed a qualitative literature review and comparative policy analysis, processing secondary data from the Central Bureau of Statistics, national surveys, and World Bank evaluation reports. The study's results indicate a policy bifurcation between Community Learning Centers (PKBM), which face structural financial and facility constraints, and the Pre-Employment Card Program, which is highly adaptive but limited to groups with adequate digital literacy. This gap fuels unequal access to sustainable learning, particularly for marginalized communities in rural areas.